2019
DOI: 10.3390/w11122608
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Variation Pattern Analysis of Hydrologic Processes and Water Quality in Three Gorges Reservoir Area

Abstract: The Three Gorges Project (TGP) has greatly enhanced the heterogeneity of the underlying surface in the Three Gorges Reservoir Area (TGRA), thereby affecting the hydrologic processes and water quality. However, the influence of the differences of underlying surfaces on the hydrologic processes and water quality in the TGRA has not been studied thoroughly. In this research, the influence of the heterogeneity of landscape pattern and geographical characteristics on the spatial distribution difference of hydrologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…The TGRA is partitioned into 26 sub-basins, as described in our previous study [53]. In order to better recognize the critical area, the whole research area was divided into left bank and right, head, middle and tail regions (as shown in Figure 1); details were given in [53].…”
Section: Model Setupmentioning
confidence: 99%
See 1 more Smart Citation
“…The TGRA is partitioned into 26 sub-basins, as described in our previous study [53]. In order to better recognize the critical area, the whole research area was divided into left bank and right, head, middle and tail regions (as shown in Figure 1); details were given in [53].…”
Section: Model Setupmentioning
confidence: 99%
“…Shen et al [52] and Shen et al [39] explored nutrient loads and causal factors from different LULC and soil types. Chen et al [53] identified the influence of the landscape pattern on the spatial distribution difference of hydrologic processes and water quality in the TGRA. Nevertheless, these studies only focused on single temporal scales.…”
Section: Introductionmentioning
confidence: 99%
“…The SWAT-VRR model divides the study area into 33 sub-basins by DEM data, each sub-basin is divided into four slope grade zones (Figure 3) consisting of 0-5 The runoff and sediment yield for 2006-2008 at the outlet of the Dapoling watershed was used to calibrate the SWAT and SWAT-VRR models, the observed data for 2009-2011 was used for model validation [62,63]. In this study, SUIF-2 algorithm in SWAT-CUP (SWAT-Calibration Uncertainty Programs) was used to perform parameter sensitivity analysis, calibration, and validation on the SWAT model and SWAT-VRR model.…”
Section: Model Calibration and Validationmentioning
confidence: 99%
“…Table 1 demonstrates the results of model calibration and validation by using observed data, the NSE and R 2 values for SWAT and SWAT-VRR in monthly and daily simulation are all above 0.6, which show a marginally good or good performance in simulating runoff and sediment yield. During model calibration, the NSE of monthly runoff sim- The runoff and sediment yield for 2006-2008 at the outlet of the Dapoling watershed was used to calibrate the SWAT and SWAT-VRR models, the observed data for 2009-2011 was used for model validation [62,63]. In this study, SUIF-2 algorithm in SWAT-CUP (SWAT-Calibration Uncertainty Programs) was used to perform parameter sensitivity analysis, calibration, and validation on the SWAT model and SWAT-VRR model.…”
Section: Model Calibration and Validationmentioning
confidence: 99%
See 1 more Smart Citation